Entrepreneurial Propensity for East Africa’s Entrepreneurs: The Impact of Failure - Abeid Salim; Xavier, Roland (Journal of Techno-Social, 2024)
The thesis explores the entrepreneurial intentions of individuals after experiencing business failure. It examines the impact of factors such as accessibility to business failure information, personal experience and demonstrated knowledge, with overall failure in business including bankruptcy and insolvency. The study is based on the Theory of Planned Behaviour (TPB), a widely recognised psychological theory that predicts human behaviour, especially in entrepreneurship. It aims to provide evidence that awareness of business failure positively influences the knowledge and perseverance of businessmen in business and other who are planning to start anew. The research shows that awareness of business failure positively influences current business owners’ intentions, enhancing their knowledge and resilience.